Implementasi Kebijakan Perda Kabupaten Gunungkidul Nomor 7 Tahun 2023 Tentang Penyelenggaraan Kepariwisataan (Studi Kasus Di Desa Wisata Argo Wijil Kalurahan Gari, Kapanewon Wonosari): Dampak Kebijakan Pariwisata terhadap Pemberdayaan Ekonomi dan Keberlanjutan di Desa Wisata Argo Wijil - noviasari, tasya; Karna Djaja, Djuniawan; Juliswara, Vibriza (LPPM STIA Lancang Kuning Dumai, 2025)
This study aims to analyze the implementation of Gunungkidul Regency Regional Regulation Number 7 of 2023 concerning Tourism Management in Argo Wijil Tourism Village. This research uses a descriptive qualitative approach by collecting data through interviews, observation, and documentation. The results show that the implementation of this policy has had a positive impact, especially on increasing economic opportunities and community empowerment. However, there are still obstacles in optimizing resources, bureaucratic coordination, and community participation. Therefore, further efforts are needed to improve communication, optimize resources, and strengthen organizational structures to achieve sustainable tourism management.